BK1 and BK2 bradykinin receptors in the rat duodenum smooth muscle. - Feres, T. (1992)
1. The dual action of bradykinin (relaxation and contraction) on the rat duodenum was investigated by studying its effect on adenosine 3':5'-cyclic monophosphate (cyclic AMP) levels in cultured duodenal smooth muscle cells, and the effects of apamin on the isolated muscle responses to agonists and antagonists of BK1 and BK2 receptors. 2. No change was observed in the cyclic AMP content of cultured cells incubated with up to 100 nM bradykinin. 3. Apamin (100-500 nM) inhibited the relaxant component and enhanced the contractile component of the responses to bradykinin and to the BK2-specific analogue [Thi5,8,D-Phe7]-bradykinin. 4. Apamin (100-500 nM) did not affect the contractile response of stretched duodenum preparation to the BK1-specific agonist des-Arg9-bradykinin. 5. The BK2 antagonist, [D-Arg0Hyp3Thi5,8,D-Phe7]-bradykinin, at a concentration which completely inhibited the relaxant response to bradykinin and to [Thi5,8,D-Phe7]-bradykinin, also prevented the contraction in response to either agonist in the presence of apamin. 6. Our results demonstrate two populations of bradykinin receptors in rat duodenum: a BK2 subtype responsible for the biphasic response of the non-stretched duodenum, and a BK1 subtype responsible for the contractile effect on the stretched tissue.